Impact of Curbside Bus-stop on Roadway Capacity in Urban Roads: Comparative Assessment of Different Methods in context of Nepal - Tiwari, Hemant; Thapa, Suraj; Sapkota, Aayushma (Journal of Engineering Issues and Solutions, 2025)
Curbside bus stops is one of the common features in urban environment targeted to public transportation users, but some time leads to reduction of capacity; hence causing traffic congestion. Hence it is utmost necessary to identify the impact of curbside bus stops on roadway capacity in urban roads. The primary data of volume, speed, density and other have been collected for one pilot corridor along urban area. As there is not specific standard for assessment of roadway capacity and hence many methods are being used in national context. This study tries to explore the impact of capacity reduction at bus stop location using Indonesian Highway Capacity Method (IHCM), Indian Highway Capacity Method (Indo HCM) and macroscopic traffic flow model.